Eficacia del grafeno en prótesis bucal. - Cantuña Chasipanta, Deysi Jacqueline (2025)
The main objective of this research was to evaluate the effectiveness of graphene in oral rehabilitation through a systematic literature review, aiming to determine its potential as an innovative material in restorative dentistry and prosthodontics. The methodology employed included a systematic review of available scientific literature from global databases, including Google Scholar, Elsevier, PubMed, SciELO, and Medigraphic. The PRISMA and PICO strategies were used to formulate the research questions. This research is classified as descriptive, cross-sectional, and retrospective, employing a qualitative approach. The studied population comprised national and international research publications on graphene in dental prosthetics. Following the inclusion criteria, 65 eligible studies were identified for analysis and selected through non-probabilistic intentional sampling. The results indicated that graphene has significant potential in fixed dental prosthetics by enhancing the materials' mechanical, aesthetic, and biological properties. Studies and clinical cases demonstrate that graphene-reinforced PMMA increases fracture resistance, durability, and biocompatibility while providing antimicrobial properties. Although further clinical validation is needed, current findings suggest that graphene could transform prosthodontics by offering patients more effective and satisfactory solutions.